2009
DOI: 10.1088/0004-637x/699/2/1395
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Measurements of the Gravitational Bending of Radio Waves Using the Vlba

Abstract: We have used the Very Long Baseline Array (VLBA) at 43, 23 and 15 GHz to measure the solar gravitational deflection of radio waves among four radio sources during an 18-day period in October 2005. Using phase-referenced radio interferometry to fit the measured phase delay to the propagation equation of the parameterized post-Newtonian (PPN) formalism, we have determined the deflection parameter γ = 0.9998 ± 0.0003 (68% confidence level), in agreement with General Relativity. The results come mainly from 43 GHz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 31 publications
3
86
0
2
Order By: Relevance
“…In a parallel study, Fomalont et al (2009) found agreement with General Relativity of 3 × 10 −4 using phase-referenced VLBA observations of 3C 279 and 3C 273 at 15, 23, and 43 GHz. Though the accuracy of their measurement does not compete with other studies, the authors pointed out that the precision of the determination of γ could be improved by scheduling specially designed VLBA experiments.…”
Section: Introductionmentioning
confidence: 58%
“…In a parallel study, Fomalont et al (2009) found agreement with General Relativity of 3 × 10 −4 using phase-referenced VLBA observations of 3C 279 and 3C 273 at 15, 23, and 43 GHz. Though the accuracy of their measurement does not compete with other studies, the authors pointed out that the precision of the determination of γ could be improved by scheduling specially designed VLBA experiments.…”
Section: Introductionmentioning
confidence: 58%
“…Shapiro et al showed the variation in the Gravitational deflection angle with respect to solar elongation angle. Fomalont et al (2009) observed position changes with respect to session and Frequency. Fomalont et al (2010) reported larger errors which cannot be explained by conventional methods and difference should be zero if the GR prediction is correct.…”
Section: Discussion On Resultsmentioning
confidence: 87%
“…In some conditions as discussed above, these bodies produce such gravitational effects on the neutrons travelling in between these bodies, these neutrons will take such will take some paths which are perpendicular to the central plane of Galaxy near the Galaxy center. Though it is heavier for my purse, purchase of new computer became necessary to take the continual computational load [21,22].…”
Section: Discussionmentioning
confidence: 99%